Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.53
|View full text |Cite
|
Sign up to set email alerts
|

Semi-supervised New Event Type Induction and Event Detection

Abstract: Most previous event extraction studies assume a set of target event types and corresponding event annotations are given, which could be very expensive. In this paper, we work on a new task of semi-supervised event type induction, aiming to automatically discover a set of unseen types from a given corpus by leveraging annotations available for a few seen types. We design a Semi-Supervised Vector Quantized Variational Autoencoder framework to automatically learn a discrete latent type representation for each see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 22 publications
0
47
0
Order By: Relevance
“…Semi-supervised learning (SSL) has attracted considerable attention to help achieve strong generalization by making use of both unlabeled data and labeled data [13,82,83,84,85,86,87,88,89]. Much research has used various SSL methods to help generate data or augment data for event extractions: role-identifying nouns [81], linear discrimination analysis [86], Vector Quantized Variational Autoencoder [85], multi-modal Generative Adversarial Network [89], etc. Distant Supervision Methods.…”
Section: Semi-supervised and Distant Supervision Methodsmentioning
confidence: 99%
“…Semi-supervised learning (SSL) has attracted considerable attention to help achieve strong generalization by making use of both unlabeled data and labeled data [13,82,83,84,85,86,87,88,89]. Much research has used various SSL methods to help generate data or augment data for event extractions: role-identifying nouns [81], linear discrimination analysis [86], Vector Quantized Variational Autoencoder [85], multi-modal Generative Adversarial Network [89], etc. Distant Supervision Methods.…”
Section: Semi-supervised and Distant Supervision Methodsmentioning
confidence: 99%
“…Previous work has shown that event-related structures are helpful in extracting new events (Lai et al, 2020) as well as discovering and generalizing to new event schemata (Huang et al, 2016(Huang et al, , 2018Huang and Ji, 2020). Hence we conduct event structure pre-training on a GNN as graph encoder to learn transferable event-related structure representations with recent advances in graph contrastive pre-training (Qiu et al, 2020;You et al, 2020;.…”
Section: Event Structure Pre-trainingmentioning
confidence: 99%
“…Nguyen and , Ding et al (2019), andYan et al (2019) introduced external knowledge to as-sist neural networks to better understand each given text. Recently, many studies applied powerful pretrained language models to better comprehend contexts (Du and Cardie, 2020;Liu et al, 2020a,b;Huang and Ji, 2020).…”
Section: Related Workmentioning
confidence: 99%